Junior high drama. The first-date dilemma - Mason, Jane B. (Stone Arch Books, 2019)
Lucia, an eigth grader at Memorial Middle School, is not looking forward to the school's first-ever boy-girl party, and wouldn't be going at all if her best friend hadn't invited her--but when she meets Adesh, she starts thinking a boy-girl party might not be so bad.